FORMULATION AND EVALUATION OF EFFERVESCENT GASTRO-RETENTIVE FLOATING TABLETS FOR CONTROLLED RELEASE OF AN ANTI-ULCER COMPOUND - Aleksandar Aleksovski (Human Research in Rehabilitation, 2013)
Effervescent floating gastro-retentive matrix tablets present novel and promising approach towards targeted and controlled drug delivery in the stomach and in the upper part of the small intestine. This kind of dosage form could be obtained by combining in a suitable ratio effervescent compounds and hydrophilic/hydrophobic polymer/s. The aim of our investigation was to develop controlled release effervescent matrix tablet which will float over the gastric media for longer than 8 hours and will release the active compound in a continuous manner over 8 hours period. We used ranitidine HCl as a model drug which has narrow absorption window in the upper small intestine, and is a good candidate for this type of dosage forms. We employed sodium bicarbonate and citric acid as effervescent compounds and two different types of hydroxypropyl methylcellulose (HPMC K4M and HPMC K15M) as a controlled release hydrophilic polymer. Three batches of tablets were produced (one containing HPMC K4M, other containing HPMC K15M, and the third containing 1:1 mixture of these two polymers) and every batch was compressed with two different forces 5.5 kN and 4.7 kN, so completely six probes of tablets were made. All six probes complied the pharmacopoeial requirements concerning mass uniformity, content, friability and hardness. All six probes tended to float fast to the surface of the medium and tend to hydrate and swell fast enough which actions provided controlled release of the compound over period of 8 hours. No significant differences in the dissolution profiles of all six probes were noticed during the investigation.